2014
DOI: 10.1111/sms.12242
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of Achilles tendon mechanical and morphological properties between both legs

Abstract: Although symmetry of Achilles tendon (AT) properties between legs is commonly assumed in research and clinical settings, different loading profiles of both legs in daily life (i.e., foot dominance) may affect the tendon properties in a side-depended manner. Therefore, AT properties were examined with regard to symmetry between legs. Thirty-six male healthy adults (28 ± 4 years), who were physically active but not involved in sports featuring dissimilar leg load participated. Mechanical and morphological AT pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 44 publications
8
56
0
Order By: Relevance
“…Differences in the cross sectional area of the TC has been reported to be larger in older age group 17 . Significant changes in the length and thickness of TC between dominant and non-dominant feet 18 as well as between right and left side 19 have been documented. Differences in the length of the tendon between dominant and non-dominant side was also confirmed in cadaveric study by Bailus et al 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Differences in the cross sectional area of the TC has been reported to be larger in older age group 17 . Significant changes in the length and thickness of TC between dominant and non-dominant feet 18 as well as between right and left side 19 have been documented. Differences in the length of the tendon between dominant and non-dominant side was also confirmed in cadaveric study by Bailus et al 20 .…”
Section: Discussionmentioning
confidence: 95%
“…Third, in Mahieu et al (2008)’s study, the left legs or ankles of their participants were evaluated, whereas we were measuring the changes of the AT on the dominant legs (right-leg dominant ( n  = 42), left-leg dominant ( n  = 3)) in response to a heel drop exercise. In fact, there are distinct loading profiles between both legs conferring asymmetric tendon properties (Bohm et al, 2015). Someone define the ball-kicking side (i.e., the leg of which we prefer most) as the dominant leg based on higher AT stiffness (Bohm et al, 2015; Siu et al, 2016), whereas higher prevalence of tendon rupture signifies dominant tendency of another leg (Chiu et al, 2016; Pang & Ying, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there are distinct loading profiles between both legs conferring asymmetric tendon properties (Bohm et al, 2015). Someone define the ball-kicking side (i.e., the leg of which we prefer most) as the dominant leg based on higher AT stiffness (Bohm et al, 2015; Siu et al, 2016), whereas higher prevalence of tendon rupture signifies dominant tendency of another leg (Chiu et al, 2016; Pang & Ying, 2006). As suggested, there are different extents of the AT stiffness changes between both legs in response to immediate weight-bearing loads, and significant changes only occur in the leg of which we prefer most (Chiu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[21] This study found no differences between the right and left side for all measurements. Bohm et al [22] showed the dominant foot's Achilles tendon length was significantly longer than the non-dominant foot. Also, they found the thickness was significantly different between the dominant and non-dominant sides.…”
Section: Anatomy • Volume 9 / Issue 3 / December 2015mentioning
confidence: 99%